High‐Definition X‐Ray Imaging of Small Gecko Skin Surface Protuberances for Digitization and 3D Printing. Issue 13 (2nd May 2018) - Green, David W.; Kelly, Stephen T.; Lee, Kenneth Ka‐Ho; Watson, Gregory S.; Watson, Jolanta A.; Jung, Han Sung
Abstract: A detailed analysis of zoological and botanical engineering structures reveals remarkable ideas for developing new healthcare technologies. One eclectic example is the surface microprotrusions of Gecko lizard skins, featuring nanoscale tips that engage in bacterial repulsion and killing. However, building biomimetic synthetic nanostructures in long range for technological use is hampered by the lack of concentrated digital information for 3D nano‐fabrication. For instance, standard micro‐computed tomography ( µ CT), confocal laser scanning microscopy (CLSM) and atomic force microscopy (AFM) imaging failed to replicate gecko spinules at the nanoscale. The authors now show that the latest generation of high‐power X‐ray microscopy (Zeiss X‐Radia 810) builds high contrast images of the gecko skin surface, and following 3D digital conversion the individual spinules, in the large array, are perfectly delineated at 150 nm and clearly featured the 50 nm nanotips crucial for bacterial cell rupturing. Consequently, the authors generate stenographic (STL.) digital file formats loaded with the instructions for 3D printing and the design blueprints for soft lithography replication. A further reconstruction of the digital data is undertaken into a 3D solid object using MeshLabs, yielding biologically realistic, virtual‐world spinule arrays. In this form, the authors are able to edit the spinules for optimal killing performance against bacterial cells. Abstract : Small scale imaging of zoological nanoscale objects is essential for translation into usable technologies. Using high power X‐ray microscopy digital copies of Gecko‐lizard nanotipped microspinules with unprecedented levels of accuracy are generated. Moreover, the X‐ray data is easily transcribed in silico for fine editing, refinement and for its real‐life projection into 3D printouts, and to provide design instructions for soft lithography replication.